Cool, Creepy, Moé: Otaku Fictions, Discourses, and Policies - Lamarre, Thomas (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2013)
This essay looks at the otaku phenomenon in terms of the production of consumption (what produces consumption, and what consumption produces) primarily three registers: fictions of otaku that stage the repression of otaku desires and identities in order to form erogenous zones; cultural discourses that pathologize otaku consumption; and government policies related to Cool Japan that strive to reconfigure otaku consumption in terms of markets and self-satisfying subjects. Considering these different registers brings into a focus a neoliberal socius or social being, which allows constant intervention into everyday life in the name of the fragility of the global free market by typologizing and pathologizing consumers.